Edith Wharton in Context : Essays on Intertextuality - Tintner, Adeline R., 1912-2003 (Book collections on Project MUSE., 2015)
Tintner provides a detailed analysis of the complex interplay between Wharton and James- how they influenced each other and how some of their writings operate as homages or personal jokes. So deeply was James in Wharton' s confidence, Tintner argues, that he provided her with source models for a number of her characters. In addition, Wharton found in his fiction structures for her own, especially for The Age of Innocence. Tintner also brings her considerable knowledge of art history to bear in her study of art allusions in Wharton' s work. Wharton' s response both to the Italian painters activ.